2011
DOI: 10.1111/j.1600-079x.2011.00856.x
|View full text |Cite
|
Sign up to set email alerts
|

A survey of molecular details in the human pineal gland in the light of phylogeny, structure, function and chronobiological diseases

Abstract: :  The human pineal gland is a neuroendocrine transducer that forms an integral part of the brain. Through the nocturnally elevated synthesis and release of the neurohormone melatonin, the pineal gland encodes and disseminates information on circadian time, thus coupling the outside world to the biochemical and physiological internal demands of the body. Approaches to better understand molecular details behind the rhythmic signalling in the human pineal gland are limited but implicitly warranted, as human chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
287
0
10

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 375 publications
(308 citation statements)
references
References 267 publications
(457 reference statements)
3
287
0
10
Order By: Relevance
“…Melatonin (N-acetyl-5-methoxytryptamine) is the most important multi-functional indole which is produced by the pineal gland and other organs [16,17]. Melatonin and its metabolites are powerful free radical scavengers with antioxidants with anti-apoptosis properties [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin (N-acetyl-5-methoxytryptamine) is the most important multi-functional indole which is produced by the pineal gland and other organs [16,17]. Melatonin and its metabolites are powerful free radical scavengers with antioxidants with anti-apoptosis properties [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Since lipid peroxidation markedly lowers its level, glutathione together with MDA are used as indicators of oxidative stress in the liver [4] . Melatonin is a serotonin-derived neurohormone formed primarily in the brain by the pineal gland of all mammals, including man [5] . In humans, melatonin is secreted mostly nocturnally.…”
Section: Introductionmentioning
confidence: 99%
“…We found that aralkylamine N-acetyltransferase (AANAT) and acetylserotonin O-methyltransferase (ASMT), the two main enzymes in melatonin synthesis, are expressed in oral mucosa and also in salivary glands. However, melatonin, which is also found in saliva, is believed to passively enter the mucous through the circulatory system in salivary glands (parotid, submaxillary and sublingual glands) [58,73]. Thus, as the quantity of melatonin entering the oral cavity is proportional to salivary flow, xerostomia, which actually aggravates periodontal status, could be associated with oral pathologies [74].…”
Section: A) Melatonin In the Oral Cavitymentioning
confidence: 99%